Pengaruh Pemberian Bobath Exercise Terhadap Perkembangan Motorik Kasar Anak Developmental Delay Di UPT Layanan Pendidikan Anak Berkebutuhan Khusus Kabupaten Gresik - Alvina Rahmawati; Nurul Halimah; Rachma Putri Kasimbara; Angria Pradita (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: This study was to identify the effect of giving Bobath Excercise on the motor development of children with Development Delay.Methods: This study used the one group pre and post test design method. In this group, the initial measurement (pre-test) was carried out and then given treatment in the form of Bobath Exercise physiotherapy intervention. After that, it was measured again (post-test) at the end of the research session to find out the response to the treatment so that the results of the experiment could be known with certainty. The independent variable in this study is the Bobath Excercise, and the dependent variable is gross motoric changes. The number of samples in this study were 15 respondents with a purposive sampling technique. Data processing in this study used SPSS software version 16.0.Results: a significance value of (0.000) which means that the P value <0.005 and it can be interpreted that the hypothesis is accepted, so it can be concluded that the effect of giving Bobath Excercise on the motor development of children with Development Delay.Conclusion: Bobath Exercises has an influence on gross motor skills with Development Delay. This is evidenced by the addition of the GMFM score from before being given the intervention and after being given the intervention.